Consensus on diagnosis and management of Cushing's disease: a guideline update. Issue 12 (December 2021) - Fleseriu, Maria; Auchus, Richard; Bancos, Irina; Ben-Shlomo, Anat; Bertherat, Jerome; Biermasz, Nienke R; Boguszewski, Cesar L; Bronstein, Marcello D; Buchfelder, Michael; Carmichael, John D; Casanueva, Felipe F; Castinetti, Frederic; et al.
Summary: Cushing's disease requires accurate diagnosis, careful treatment selection, and long-term management to optimise patient outcomes. The Pituitary Society convened a consensus workshop comprising more than 50 academic researchers and clinical experts to discuss the application of recent evidence to clinical practice. In advance of the virtual meeting, data from 2015 to present about screening and diagnosis; surgery, medical, and radiation therapy; and disease-related and treatment-related complications of Cushing's disease summarised in recorded lectures were reviewed by all participants. During the meeting, concise summaries of the recorded lectures were presented, followed by small group breakout discussions. Consensus opinions from each group were collated into a draft document, which was reviewed and approved by all participants. Recommendations regarding use of laboratory tests, imaging, and treatment options are presented, along with algorithms for diagnosis of Cushing's syndrome and management of Cushing's disease. Topics considered most important to address in future research are also identified.